Risk factors influencing the incidence of perineal rupture in normal delivery - Darlina, Darlina; Hakim, Dzulfikar Djalil Lukman; Mose, Johanes C.; Sukarsa, Mochamad Rizkar Arev; Krisnadi, Sofie Rifayani; Susiarno, Hadi (Science Midwifery, 2025)
Perineal rupture is a common complication during vaginal delivery and can lead to long-term health consequences for the mother. This study aims to identify the risk factors associated with perineal rupture in normal vaginal delivery. A scoping review was conducted by analyzing relevant literature from 2020 to 2024. The results indicate that major risk factors for perineal rupture include birth weight, parity, duration of the second stage of labor, and the use of obstetric instruments. Additionally, pregnancy exercise and perineal massage were found to be effective in reducing the incidence of perineal rupture, particularly in primiparous women. Proper management of labor, including monitoring fetal weight and employing appropriate medical techniques, plays a significant role in minimizing the risk of perineal rupture. This study recommends the implementation of evidence-based preventive measures to reduce the prevalence of perineal rupture and its long-term impacts on maternal health.